2020
DOI: 10.1248/bpb.b20-00034
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of the Traditional Chinese Medicine <i>Ephedra sinica granules</i> on <i>Streptococcus pneumoniae</i> Pneumolysin

Abstract: Streptococcus pneumoniae (S. pneumoniae) is an opportunistic pathogen that causes pneumonia, meningitis and bacteremia in humans and animals. Pneumolysin (PLY), a major pore-forming toxin that is important for S. pneumoniae pathogenicity, is a promising target for the development of anti-infective agents. Ephedra sinica granules (ESG) is one of the oldest medical preparation with multiple biological activities (such as a divergent wind and cold effect); however, the detailed mechanism remains unknown. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Ephedrine hydrochloride and Pseudoephedrine hydrochloride are phenethylamines from Ephedra sinica granules [ 86 ] and MXSGT (Ma-xing-shi-gan-tang) [ 87 ] are compounds obtained from plants used in traditional Chinese medicine. All of them seem to inhibit the oligomerization of the toxin, although more studies are necessary to specify which residues of PLY are involved.…”
Section: Resultsmentioning
confidence: 99%
“…Ephedrine hydrochloride and Pseudoephedrine hydrochloride are phenethylamines from Ephedra sinica granules [ 86 ] and MXSGT (Ma-xing-shi-gan-tang) [ 87 ] are compounds obtained from plants used in traditional Chinese medicine. All of them seem to inhibit the oligomerization of the toxin, although more studies are necessary to specify which residues of PLY are involved.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of other natural compounds have identified chemical moieties important to blocking of PLY hemolytic activity and perhaps to the design of future inhibitors of PLY (Li et al, 2017). Similar studies have also reported prevention and attenuation of pneumococcal infection using compounds that prohibit PLY oligomerization (Li et al, 2020;Lv et al, 2020;Xu et al, 2020). These compounds potentially show promise as tools for developing small molecule adjuvant therapies in the prevention or treatment pneumococcal infection and studying PLY interactions.…”
Section: Pneumolysin As a Therapeutic Targetmentioning
confidence: 88%
“…Artemisinin, an active molecule isolated from Artemisia annua Linn., has saved the lives of millions of people suffering from malaria [12] , [13] . Compared to the existing antibiotics, antimicrobial compounds from traditional Chinese medicine have better bactericidal activity and can reverse multidrug resistance in bacteria [14] , [15] . For example, Scutellaria baicalensis extracts may be effective against inflammation and Salmonella enteritidis infection [16] .…”
Section: Introductionmentioning
confidence: 99%